SHOULD CHILDREN AND ADOLESCENTS BE TESTED FOR HUNTINGTON’S DISEASE? ATTITUDES OF FUTURE LAWYERS AND PHYSICIANS IN SWITZERLAND - Elger, Bernice S. (Bioethics, 2006)
The objective of the study was to identify future lawyers’ and physicians’ views on testing children for Huntington’s disease (HD) against parents’ wishes. After receiving general information about HD, patient autonomy and confidentiality, law students and advanced medical students were shown an interview with a mother suffering from HD who is opposed to informing and testing her two children (aged 10 and 16) for HD. Students then filled out questionnaires concerning their agreement with testing. No significant differences were found between medical and law students or between students from different courses concerning the adolescent son. Three quarters of students thought that he should be told about his mother’s disease, and 91% thought the adolescent son should have the opportunity of genetic testing for HD for himself. However, significant differences were found concerning the 10-year old son, with 44% of law students and 30% of medical students in favour of testing the child for HD. Students raised some important ethical issues in their elective comments. In conclusion, we found highly positive attitudes towards informing a 16-year old of his mother’s HD and offering to test him. These attitudes were not in tune with guidelines. Students did not consider several practical and ethical issues of genetic testing of children and adolescents. Specific education should ensure that attitudes are based on sufficiently detailed knowledge about all aspects of genetic testing of children to discourage pressures on persons at risk of HD.